KBAD-A Real Time Opportunity for Sustainability Education During Covid-19 - Selina Nargis; Muhammad Rehan Dastagir; Ferdous Ahmed; Sayma Akhter; Mohammed Ataur Rahman (Journal of Sustainability Perspectives, 2022)
In achieving Sustainable Development Goals, the university holds a leading position. However, throughout the year long pandemic attachment between university and student has moved towards a more virtual platform. It has become a great challenge for both students’ and educational institutions to continue education through online platform. Facing the challenges of pandemic IUBAT successfully continues the online educational program. KBAD-Knowledge Based Area Development, a UNU (United Nations University) Flagship project has proven effectiveness in building links with IUBAT to students across the country. This program is to produce at least one technical graduate from 87,963 villages of Bangladesh. Door to door proper guidance for higher education is provided in the remote villages with financial assistance and interest free loans for the meritorious and needy. Since 2010, a total 9,381 students have graduated and another 11,699 are currently studying under KBAD from 535 out of 550 Upazilas and Thanas across the country. In the year of 2018, Merit Scholarship has been given approximately BDT 164.9 million; Interest free loan approximately BDT 20 million; Special Scholarship BDT 0.66 million with a total sum 185.56 million BDT or 2.2 m USD. Generally, 15% (Fifteen) more scholarship has been given to female students to ensure gender equity.  There is no other such university sponsored scheme/program for financial loan available in the country.  In the period of COVID-19, an additional 15% (fifteen) tuition fee waiver has been given to all, admission fee reduced 50%, a 6 USD fund transferred to the students to avail mobile data. Students have graduated with technical and ESD (Education for Sustainable Development) skills as it is a mandatory practice of this university. This nationwide education promotion made it a sustainable campaign outreaching the majority of remote villages of the country and encouraging technical education to the underprivileged group of the society along with the urban students. This unique program complies with SDG goals 4.3, 4.4 and 4.7. These goals ensure equal access of affordable, technical, tertiary and sustainable education to all leaving no one behind. KBAD is a model to eradicate educational discriminancy in a nation by removing financial barriers in tertiary education.Keyword: Sustainability Education, KBAD, Education Loan, Equal Access of Tertiary Education, Mentoring Rural Students